A Spotlight on the Compatibility between XFEL and Ab Initio Structures of the Oxygen Evolving Complex in Photosystem II. Issue 29 (25th April 2017) - Narzi, Daniele; Mattioli, Giuseppe; Bovi, Daniele; Guidoni, Leonardo
Abstract: The Mn4 CaO5 cluster of photosystem II promotes a crucial step in the oxygenic photosynthesis, namely, the water‐splitting reaction. The structure of such cluster in the S1 state of the Kok–Joliot's cycle has been recently resolved by femtosecond X‐ray free‐electron laser (XFEL) measurements. However, the XFEL results are characterized by appreciable discrepancies with previous X‐ray diffraction (XRD), as well as with S1 models based on ab initio calculations. We provide here a unifying picture based on a combined set of DFT‐based structures and molecular dynamics simulations of the S0 and S1 states. Our findings indicate that the XFEL results cannot be interpreted on the grounds of a single structure. A combination of two S1 stable isomers together with a minority contribution of the S0 state is necessary to reproduce XFEL results within 0.16 Å. Abstract : Shedding light into the water‐splitting cycle of photosystem II : DFT calculations indicate that the recent X‐ray free‐electron laser (XFEL) structure of photosystem II complex cannot be interpreted on the grounds of a single structure: two S1 isomers may coexist together with a minority contribution of the S0 state.